145k views
5 votes
3(6+5y)=2(-5+4y) help huhu

User Matt Welke
by
4.9k points

2 Answers

5 votes

Answer:

y = -4

Explanation:

distribute both 3 and 2 through the parenthesis, move the variable to the left side and change its sign, move constant to the right side and change its sign, collect like terms, calculate the difference, divide both sides of the equation by 7, and your answer would be -4

User Vickyonit
by
4.6k points
2 votes

Answer:

-4 = y

Explanation:

3(6+5y)=2(-5+4y)

18 + 15y = -10 + 8y

+10 +10

28 + 15y = 8y

- 15y -15y

28 = - 7y

28/-7 = -4

-7y/-7 = y

User RunningRhetoric
by
4.9k points